PENGARUH CUSTOMER EXPERIENCE DAN STORE ATMOSPHERE TERHADAP LOYALITAS PELANGGAN DI CV. ARY’S MIKRO SINGAPADU BALI - Suwardyanba, Gede Irfan; Prawitasari, Putu Putri; Ngurah Oka Ariwangsa, I Gusti; Tirtayani, I Gusti Ayu (LP2M Universitas Bina Bangsa, 2025)
The purpose of this study is to test how CV customer service is. Ary's Mikro Singapadu Bali and the atmosphere of the store affect customer loyalty. One hundred participants, all of whom are active in CV. Ary's Micro, participated in this quantitative study that used a purposeful sample strategy. The data were analyzed using multiple linear regression after being collected using a Likert-based questionnaire. To determine how much the two independent factors affect customer loyalty at the same time, we used the F test; To separate the effects, we use the T test. A regression coefficient of 0.439 and a significance level of 0.001 (less than 0.05) indicate that Customer Experience significantly and positively affects Customer Loyalty. The regression coefficient of 0.227 and the significance level of 0.001 (less than 0.05) indicate that the atmosphere of the store positively and significantly affects customer loyalty. The two factors have a substantial impact on consumer loyalty when taken together, according to the F test, which shows a significance level of 0.001. These results highlight the importance of making customers feel comfortable and have good interactions to increase customer loyalty. By promoting retail strategies based on innovation in consumer contact and retail environmental management, the study helps achieve Sustainable Development Goal (SDG) 8, which focuses on Decent Work and Economic Growth. The findings of this study have important practical implications, such as the recommendation that CVs. Ary's Micro is constantly working to improve the Store Atmosphere and Customer Experience to increase customer loyalty.